Hak Waris Anak Hasil Surogasi Menurut Peraturan Perundang–Undangan di Indonesia - Ruby Harland, Shanaz (CV. Era Digital Nusantara, 2023)
The aim of this research is to find out whether there are women who do not have a uterus or cannot undergo pregnancy due to medical indications and want to have children and what the legal status of inheritance is regarding the surrogate mother. This paper uses a normative method by analyzing and using a legal approach regarding the data sources used, namely secondary data sources consisting of primary legal materials, secondary legal materials and tertiary legal materials (Hadi, 1990). The data collection method uses literature study and review of applicable legal regulations. The data analysis carried out by the author is qualitative analysis. The results of the research show that renting a womb cannot be carried out in Indonesia because it violates Law Number 1 of 1974 concerning marriage, where to obtain legal offspring there must be a marriage bond. This applies if the surrogate woman is a widow or maiden. Womb rental also violates Article 72. Law Number 36 of 2009 concerning Health, the womb rental agreement/agreement from a civil law perspective is considered invalid because it violates the essence of the object of the agreement/agreement. The inheritance status of children resulting from renting a womb in the perspective of Islamic law is that children resulting from renting a womb are classified as illegitimate children who are not recognized or children resulting from adultery, if the surrogate mother has the status of a widow or girl, because in inheritance law which causes inheritance between the heir and the heir, namely there is a kinship and marriage relationship, while a child born to a surrogate mother does not have a marriage relationship.